Design by nature interaction between nature and design/architecture in Norway - Bengtsson, Staffan; Zetterstrèom, Jelena; Barnett-Lindberg,Angela (Stockholm Arvinius Fèorlag, 2011)
The book takes as its starting point the fact of nature and mankind having seriously renewed their tryst. Not sincethe close of the 19th century has the desire for interaction with nature been as powerful as it is today. A whole galaxy of Norwegian architects, many of them involved with theNational Tourist Route Project, and designers are now cultivating this new interconnetion between man and his landscape. Under the shadow of climate change and excessive consumption, a strong passion for originality and roots is now awakening. "Design by nature" tells this exciting story from a Norwegian design perspective. The second part of the bookcovers design and architecture in present-day Norway.
Keywords: Design -- Norway; Architecture -- Norway